A Dipole Sub-Array With Reduced Mutual Coupling for Large Antenna Array Applications - Muhammad Ali Jamshed; Osama Amjad; Moazam Maqsood; Masood Ur Rehman; Dushantha Nalin K. Jayakody; Haris Pervaiz (IEEE Access, 2019)
The use of large array antennas in multiple-input multiple-output (MIMO) exploits diversity and reduces the overall transmission power making it a key enabling technology for 5G. Despite all the benefits, mutual coupling (MC) between elements in these array antennas is a concerning issue as it affects the antenna terminal impedance, reflection coefficients, etc. In this paper, a four-element printed dipole sub-array with reduced MC for S-band has been proposed. A balanced transmission line structure has been designed with two dipole arms on the opposite side of the substrate. Simulated and measured results are in good agreement making the design suitable for large array applications such as phased array radars. The proposed array exhibits good impedance matching with a reflection coefficient of -45 dB and resonating at the center frequency of 2.8 GHz. Moreover, isolation of -20 dB has been achieved for each element in a 2×2 planar array structure using out of band, parasitic elements, and planar shift by distributing the separation between the elements.